New versus frequent donors: Exploring the behaviour of the most desirable donors. Issue 3 (August 2016) - Faulkner, Margaret; Romaniuk, Jenni; Stern, Philip
Highlights: We examine longitudinal money and blood donor behaviour, drawing on two databases with records of over 1 million donors. The vast majority of new donors give once or twice a year with few giving at higher frequency levels. Only 50% of frequent donors continue this behaviour in the subsequent year, with the churn level stable. Results warn against over investing in very frequent donors, whereas encouragement of once-a-year behaviour is important. Abstract: While there is no shortage of worthy recipients for prosocial behaviour, there is a constant battle to attract and keep donors. This research examines both money and blood donor behaviour for two key groups, new donors, (to grow the donor base), and frequent donors (to secure current support streams). We draw on over 1.2 million records from a U.S. health related charity for a three-year timeframe; and records of all Australian blood donors (1.1 million) for a five-year timeframe. We show the law-like patterns that underpin brand growth in other markets also apply in the non-profit sector. The vast majority of new donors give just once or twice a year with few giving at higher frequency levels. The stability of donation churn across blood and money suggests a structural norm in behaviour over time rather than an outcome of marketing activity. We discuss implications for resource allocation and marketing strategies. Chinese Abstract: 亲社会行为不乏合资格的领受者，但要吸引和留住捐助者却常常要下大力气。 本研究考察了两个重点人群——即新的捐献者（为扩大捐献者数目）和频繁捐献者（为巩固当前的支持人群）的捐钱和捐血行为。从美国一家与健康有关的慈善机构抽取三年时间范围内的120多万条记录；以及五年时间范围内的所有澳大利亚捐血者（110万）的记录。我们展示出定律性的规律，这些规律常在其他市场巩固品牌成长， 同时也适用于非盈利行业。 绝大多数新捐血者每年只捐一到两次，但鲜有捐献更多次数者。 捐血者和捐钱者的稳定性表明行为的结构性准则随时间变化，而非营销活动的结果。 我们讨论了资源分配和营销策略的影响。